ALGORITMA GENETIKA UNTUK MENYELESAIKAN COIN PROBLEM: APLIKASI PADA MESIN ATM - Elliana Gautama (Universitas Sriwijaya, 2016)
AbstractAt the present in Indonesia an Automatic Teller Machine (ATM) only able to withdraw specific denomination, such as Rp. 50.000 or Rp. 100.000. Sometimes, client wants to withdraw specific denomination but the ATM only provides Rp. 100.000 or other denomination, then the client have to switch to other ATM and sometime they have to walk so far to withdraw specific denomination in ATM as they wants. The main obstacle at present is the absence of an algorithm application of ATM that can cope problem to solve value of money to combination of denomination of money as client wants. This problem was called Coin Change Problem and it is usually used to find optimal combination from many different money combinations. This paper will use the theory of Genetic Algorithms to solve the Coin Change Problem. Genetic algorithm is computational algorithm was inspired by evolution theory then was adopted from it self and it was become computational algorithm to find solution from problem in natureâ€™s way. One of application genetic algorithm is the combination of optimization problems, which get a value of an optimal solution to a problem that has many possible solutions. With this Genetic Algorithm in this paper is the resolve to the Coin Change Problem on application of ATM, so that an ATM can issued a optimal combination from many different money combinations. In this study developed an algorithm using Genetic Algorithm which can solve the problems of Coin Problem in ATM applications, resulting in an ATM can issue some money with a optimum combination specific denomination. Keywords : Genetic Algorithms , Coin Problem , Optimization Combination , ATMAbstrakPada saat ini di Indonesia, sebuah mesin ATM untuk fasilitas penarikan uang tunainya hanya dapat mengeluarkan satu jenis pecahan mata uang saja, misalnya pecahan 50.000 rupiah saja atau pecahan 100.000 rupiah saja, sedangkan ada saatnya seorang nasabah memerlukan beberapa jenis pecahan mata uang dalam satu kali transaksi tanpa berpindah mesin ATM. Mesin ATM saat ini walaupun hanya dapat mengeluarkan satu jenis pecahan mata uang saja, sebenarnya memiliki tempat untuk beberapa pecahan mata uang. Permasalahan untuk memecahkan kasus tersebut di dalam algoritma disebut dengan Coin Problem.Coin Problem ini berguna untuk memecahkan masalah dalam mencari jumlah kombinasi pecahan optimum untuk mendapatkan sejumlah nilai uang yang diinginkan dengan kombinasi beberapa pecahan mata uang yang berbeda. Untuk memecahkan masalah Coin Problem ini penulis menggunakan Algoritma Genetika. Algoritma genetika adalah algoritma komputasi yang diinspirasi teori evolusi yang kemudian diadopsi menjadi algoritma komputasi untuk mencari solusi suatu permasalahan dengan cara yang lebih â€œalamiahâ€.Berdasarkan hasil pengujian yang telah dilakukan terbukti bahwa dengan menggunakan Algoritma Genetika dapat menyelesaikan permasalahan Coin Problem dalam Aplikasi Mesin ATM, sehingga dalam satu mesin ATM dapat mengeluarkan kombinasi jumlah pecahan mata uang yang optimum.Kata Kunci : Algoritma Genetika, Coin Problem, Optimasi Kombinasi, mesin ATM.